Ultra-endurance exercise is associated with extensive inflammatory cell infiltration in human skeletal muscle of experienced athletes - Wahlin-Larsson, B.; Marklund, P.; Mattson, C. M.; Ponsot, E.; Lindvall, B.; Ekblom, B.; Kadi, F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
As ultra-endurance exercises impose an extreme physiological stress reflected by high levels of systemic inflammatory markers (Kim et al., 2007; Kim et al., 2009), it is hypothesized that skeletal muscle can be the site of an important inflammatory reaction. To our knowledge, the effects of very prolonged endurance exercise on local skeletal muscle inflammation have not been examined. The aim of this study was to assess the effects of a single 24 h ultra-endurance exercise bout followed by a 28 h recovery period on local muscle and systemic inflammatory responses in well trained ultra-endurance athletes. Method: Blood and muscle samples were collected before (PRE), immediately after the exercise (POST) and after 28h of recovery (POST28). CRP and several inflammatory cytokines were assessed together with the evaluation of the occurrence of inflammatory cells (CD3+, CD8+, CD68+) and the expression of major histocompatibility complex class-I (MHC class-I) in skeletal muscle. Result: A major finding was the occurrence of an extensive inflammatory cell infiltration in skeletal muscle of all athletes and the number of CD3+, CD8+ and CD 68+ cells were 2-3 fold higher at POST28 compared to PRE (P<0.05). The inflammatory cell infiltration was associated with a significant increase in the expression of MHC class-I in muscle fibers. At POST, the levels of IL-6, IL-8 and CRP were significantly increased. At POST28, IL-8 and CRP continued to increase. There were no significant associations between the magnitude of the systemic and local muscle inflammatory reactions. Discussion: In conclusion, an endurance activity at a low intensity (~60% VO2max) but sustained over a very prolonged period (24 h) induces an extensive infiltration of inflammatory cells in skeletal muscle of well-trained athletes 28 h after termination of the exercise bout. The concomitant systemic inflammation usually reported after such exercises (Neubauer et al., 2008; Suzuki et al., 2003), was not correlated with the amplitude of the local muscle inflammatory reaction.